Renal Cell Carcinoma in Transplanted Kidney: A Case Report and Literature Review - Borga, Ana Lavratti (2022)
Introduction: The incidence of renal cell carcinoma in the transplanted kidney is extremely rare. Case report: A 42-year-old female underwent a living-related donor kidney transplant from her 60-year-old mother due to glomerulonephritis leading to end-stage renal disease.Ultrasonography,nine years after transplantation, revealed a lower pole renal tumor in the renal graft with a suspicious image of malignant neoplasm on computed tomography. The patient underwent partial nephrectomy and histological analysis revealed clear cell carcinoma. Final considerations: After one year of follow-up, serum creatinine levels are normal and there are no signs of metastasis or tumor recurrence.